Decolonizing Counseling Practice: Multicultural Innovations and Social Justice in a Systematic Review of Scopus Database Study - Bakhtiar, Muhammad Ilham; Hasbahuddin; Edil Wijaya Nur; Ida Zahara Adibah; I Ketut Wisarja; Salim Korompot (International Journal of Multicultural Counseling and Development, 2025)
This study aims to (1) identify research trends in multicultural counseling innovations based on Scopus data from 2019–2025, and (2) explore the decolonization of counseling practices through a systematic analysis of the development of multicultural competence and social justice in counseling psychology. This inquiry is particularly relevant as universal counseling models rooted in Western norms are increasingly regarded as insufficient to address the diverse needs of global societies. The focus is directed toward understanding how decolonization challenges the dominance of Western perspectives, incorporates local wisdom, and promotes the role of counselors as agents of social advocacy. A systematic literature review was conducted on 173 Scopus-indexed articles published between 2019 and 2025, with screening procedures guided by the PRISMA framework. The findings demonstrate that multicultural counseling innovations have advanced through multiple approaches, including culturally responsive cognitive behavioral therapy (CBT), systematic adaptation models such as the Southampton Adaptation Framework, and the integration of traditional practices rooted in indigenous communities. The study further reveals that the effectiveness of psychological interventions is largely determined by the extent of cultural adaptation, while inadequate adaptation risks reproducing bias and reinforcing social inequities. In conclusion, decolonizing counseling emerges as a transformative paradigm that emphasizes the integration of indigenous knowledge, critical awareness of systemic injustice, and the counselor’s role as a catalyst for social change. These insights carry significant implications for advancing inclusive counseling theories and developing contextually grounded practices that respond effectively to multicultural societies in the era of globalization.